Kyoshi’s Individuation Process in F. C. Yee’s Avatar: The Rise of Kyoshi - Salsabilarahma, Annida Sefia (LITERA KULTURA : Journal of Literary and Cultural Studies, 2024)
This study aims to examine the individuation process of Kyoshi, the main character in F. C. Yee's novel Avatar: The Rise of Kyoshi, on her journey to self-realization as the Avatar. This research employs a qualitative model based on Carl Jung's theory of individuation. In order to obtain the results, the researcher examined five archetypes of Kyoshi's individuation process, namely persona, shadow, ego, animus, and self. The researcher gathered data from a variety of sources, including narration, dialogue, monologues, and contextual information from the novel. This research presents findings on Kyoshi's archetypes, indicating that she has successfully completed the individuation process as the Avatar. This study is anticipated to offer insights for further research examining novel characters using a psychoanalytic approach, particularly Carl Jung's individuation process theory. Keywords: Carl Jung, individuation process, archetype, psychoanalysis